USO DE MICRO-ORGANISMOS PARA A BIORREMEDIAÇÃO DE AMBIENTES IMPACTADOS - Pereira, Aline Ramalho Brandão; Freitas, Diego Antônio França de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704818 In the last decade the environment problems have being more critical and frequent,mainly due to the population growth and the increase of industrial activities. The observation ofmicrobial answer to the human environmental intervention, shows the capacity of theseorganisms in degrading the pollutant and its utilization as source of nutrients. Therefore, the useof microorganisms in degrading the pollutant presents in polluted areas is called bioremediation.The main of these project is join some papers that justify the use of microorganisms in theremediation of polluted areas, as a didactic tool in the environmental education at universities.